Travel and tourism in Britain, 1700-1914.
1 online resource (2048 pages).
Keywords: The British led the way in holidaymaking. This four-volume primary resource collection brings together a diverse range of texts on the various forms of transport used by tourists, the destinations they visited, the role of entertainments and accommodation and how these affected the way that tourism evolved over two centuries.Volume 1: Travel and Destinations Texts in this volume draw on accounts by early travellers, from short factual lists to longer subjective descriptions. Documents show how eagerly new forms of transport were adopted and how they gave rise to different leisure activities and new destinations. Methods of travel covered include: early road travel by horse or wagon, river travel via sail and steamships, railways, the safety bicycle, motorized transport (charabancs, coaches, buses, cars and bicycles) and finally, air travel.